NURSING CARE WITH THE MAIN PROBLEM OF FEVERTYPHOID (Medical Studies and Health Journal (SEHAT), 2024)
Fevertyphoid is a disease caused by infection with the bacteria Salmonella typhi. This disease is still a health problem, especially in developing countries. This disease is closely related to personal hygiene and the surrounding environment, such as the use of clean water, waste management and disposal. Transmission of fevertyphoid It can be fecal and oral which enters the human body through contaminated food and drink. The general aim of this journal is to describe the management of nursing care with the main problem of fevertyphoid. This case study uses a descriptive method, namely describing the nursing care process by focusing on one of the important problems in the selected case, namely nursing care with the main problem being fever.typhoid.